Formation and development of cavitation in a transparent nozzle with double orifices on different planes. Issue 2 (1st June 2023) - Ma, Jinglong; Wen, Hua; Jiang, Shuisheng; Jiang, G.
ABSTRACT: In this paper, the formation and development of cavitation in a transparent nozzle with double orifices on different planes are studied through a visual transparent nozzle experiment. The effect of different injection conditions on the formation and development of cavitation are analyzed. The results demonstrate that with a decrease in needle valve lift and an increase in injection pressure, the amount of cavitation is augmented, which significantly improves the energy utilization efficiency and reduces the emission of harmful substances. The instantaneous and mean images reveal that cavitation in the nozzle presents clear cycle-to-cycle variation and that string cavitation is related to the geometry of nozzle.